Glypican 6 Enhances N-Methyl-D-Aspartate Receptor Function in Human-Induced Pluripotent Stem Cell-Derived Neurons - Sato, Kaoru; Takahashi, Kanako; Shigemoto-Mogami, Yukari; Chujo, Kaori; Sekino, Yuko (Frontiers in Cellular Neuroscience, 2016)
The in vitro use of neurons that are differentiated from human induced pluripotent stem cells (hiPSC-neurons) is expected to improve the prediction accuracy of preclinical tests for both screening and safety assessments in drug development. To achieve this goal, hiPSC neurons are required to differentiate into functional neurons that form excitatory networks and stably express N-methyl-D-aspartate receptors (NMDARs). Recent studies have identified some astrocyte-derived factors that are important for the functional maturation of neurons. We therefore examined the effects of the astrocyte-derived factor glypican 6 (GPC6) on hiPSC-neurons. When we pharmacologically examined which receptor subtypes mediate L-glutamate (L-Glu)-induced changes in the intracellular Ca2+ concentrations in hiPSC neurons using fura-2 Ca2+ imaging, NMDAR-mediated responses were not detected through 7 days in vitro (DIV). These cells were also not vulnerable to excitotoxicity at 7DIV. However, a 5-d treatment with GPC6 from 3DIV induced an NMDAR-mediated Ca2+ increase in hiPSC-neurons and increased the level of NMDARs on the cell surface. We also found that GPC6-treated hiPSC-neurons became responsive to excitotoxicity. These results suggest that GPC6 increases the level of functional NMDARs in hiPSC-neurons. Glial factors may play a key role in accelerating the functional maturation of hiPSC neurons for drug-development applications.